Disorders of orgasm: definitions and epidemiology - Кочарян, Г. С. (Psychological Counseling and Psychotherapy, 2017)
Various definitions of orgasmic disorders in women and men, the terminology used to indicate their different forms, dynamics of ideas on these disorders and the frequency of anorgasmia revealed in various studies are submitted